Answers

2014-10-23T16:24:04+05:30





1) L.H.S = 1*1/3(6x+24) = 2x+8         ----------- eq.1
    R.H.S = -1/4(12x-72)+20 = -3x+38  -----------eq.2
Now equate L.H.S and R.H.S
   2x+8 = - 3x+38
2x+3x = 38-8
    5x   = 30
      x   =  30/5
      x   =   6
0
2014-10-23T16:30:22+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
1.
 \frac{1}{3}(6x+24)= \frac{-1}{4} (12x-72)+20

 \frac{1}{3}*6x+ \frac{1}{3}*24= \frac{-1}{4}*12x- \frac{-1}{4}*(-72)   +20

2x + 8 = -3x+18+20
2x+3x=18+20-8
5x=30
x= \frac{30}{5}=6

2.
 \frac{5}{6x} + \frac{3}{8x} =2+ \frac{1}{3x}

 \frac{20+9}{24x} = \frac{6x+1}{3x}

 \frac{29}{24x} = \frac{6x+1}{3x}

3x*29=24x*(6x+1)
87x=144 x^{2} +24x
87x-24x=144 x^{2}
63x=144x^{2}

⇒ x= \frac{63}{144}

x \neq 0 as the denominator can't be zero.

1 5 1
5/6x
means 5/(6x), right?
yes
then the answer is corect...
i checked it.